2009
DOI: 10.1371/journal.pone.0007158
|View full text |Cite
|
Sign up to set email alerts
|

miR-155 Inhibition Sensitizes CD4+ Th Cells for TREG Mediated Suppression

Abstract: BackgroundIn humans and mice naturally occurring CD4+CD25+ regulatory T cells (nTregs) are a thymus-derived subset of T cells, crucial for the maintenance of peripheral tolerance by controlling not only potentially autoreactive T cells but virtually all cells of the adaptive and innate immune system. Recent work using Dicer-deficient mice irrevocably demonstrated the importance of miRNAs for nTreg cell-mediated tolerance.Principal FindingsDNA-Microarray analyses of human as well as murine conventional CD4+ Th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 30 publications
7
56
0
Order By: Relevance
“…We observed that among the miRNAs that were dysregulated in response to SEB, miR-155 was one of the most significantly altered. It has been reported that naive CD4 ϩ T cells initially display low levels of miR-155, which is increased after the engagement of TCR by an antigen (28,29). This is consistent with our observation that miR-155 was upregulated following SEB activation.…”
Section: Discussionsupporting
confidence: 93%
“…We observed that among the miRNAs that were dysregulated in response to SEB, miR-155 was one of the most significantly altered. It has been reported that naive CD4 ϩ T cells initially display low levels of miR-155, which is increased after the engagement of TCR by an antigen (28,29). This is consistent with our observation that miR-155 was upregulated following SEB activation.…”
Section: Discussionsupporting
confidence: 93%
“…[66][67][68][69] Thus, up-or downregulation of specific miRNAs in Tregs could be a new therapy method used to treat GVHD patients in clinical trials. Here, we confirm another pathway miR-146b-5p-TRAF6-NF-kB could also contribute to this area.…”
Section: Cd4mentioning
confidence: 99%
“…16 It also indirectly limits overactivation of Th1 cells by regulating Treg cell function. 13 miR-155 is upregulated in activated immune cells 17 and modulates immune responses by regulating cell differentiation (such as Th1 and Treg) and cytokine secretion (such as tumor necrosis factor-alpha) and IL-6). [18][19][20] However, we found that miR-155 was downregulated in patients with ACS, which was consistent with what Fichtlscherer et al 21 found in patients with coronary artery disease.…”
Section: The Altered Expression Of Mirnas In Patients With Acsmentioning
confidence: 99%